If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -7)(2x + 1) = 10x(x + -4) Reorder the terms: (-7 + 5x)(2x + 1) = 10x(x + -4) Reorder the terms: (-7 + 5x)(1 + 2x) = 10x(x + -4) Multiply (-7 + 5x) * (1 + 2x) (-7(1 + 2x) + 5x * (1 + 2x)) = 10x(x + -4) ((1 * -7 + 2x * -7) + 5x * (1 + 2x)) = 10x(x + -4) ((-7 + -14x) + 5x * (1 + 2x)) = 10x(x + -4) (-7 + -14x + (1 * 5x + 2x * 5x)) = 10x(x + -4) (-7 + -14x + (5x + 10x2)) = 10x(x + -4) Combine like terms: -14x + 5x = -9x (-7 + -9x + 10x2) = 10x(x + -4) Reorder the terms: -7 + -9x + 10x2 = 10x(-4 + x) -7 + -9x + 10x2 = (-4 * 10x + x * 10x) -7 + -9x + 10x2 = (-40x + 10x2) Add '-10x2' to each side of the equation. -7 + -9x + 10x2 + -10x2 = -40x + 10x2 + -10x2 Combine like terms: 10x2 + -10x2 = 0 -7 + -9x + 0 = -40x + 10x2 + -10x2 -7 + -9x = -40x + 10x2 + -10x2 Combine like terms: 10x2 + -10x2 = 0 -7 + -9x = -40x + 0 -7 + -9x = -40x Solving -7 + -9x = -40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40x' to each side of the equation. -7 + -9x + 40x = -40x + 40x Combine like terms: -9x + 40x = 31x -7 + 31x = -40x + 40x Combine like terms: -40x + 40x = 0 -7 + 31x = 0 Add '7' to each side of the equation. -7 + 7 + 31x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 31x = 0 + 7 31x = 0 + 7 Combine like terms: 0 + 7 = 7 31x = 7 Divide each side by '31'. x = 0.2258064516 Simplifying x = 0.2258064516
| -8x^2+46x-30=17 | | 6x-2x+8=+5+8 | | 8x-x^2=24 | | 16(x+3)=7(x-5)-9(x+4)-7 | | 6x^2-48x=36 | | 11a^3-11a= | | -32x=34x-x+1 | | 3x^2*18x+37=0 | | ny+mx=c | | x^2+20x-78=0 | | -4=6x-10x | | p=2.50(200)-500 | | 5x^2-180= | | 2[5x-10]+17=37 | | -3x^2+10x+8=0 | | X-x+6=2(x+3) | | 2(x-1.5)=2x-3 | | 12y=3+x | | -2(3x-5)=-110 | | 60x=30x+40x | | -2(3x-5)=-10 | | 56x+127=21 | | 2x-22=54 | | H=-16t^2+30t+78 | | 8x=2x-10x | | X=x-7 | | 32x^2y-2y=0 | | 16s^2-100=0 | | 12x^4+30x^3+12x^2=0 | | -8x=2x-10x | | 5x^2-65x-10=0 | | 5(x+2)=2x+3x+10 |